Effects of Whole-Body Electromyostimulation on Strength-, Sprint-, and Jump Performance in Moderately Trained Young Adults: A Mini-Meta-Analysis of Five Homogenous RCTs of Our Work Group - Wirtz, Nicolas; Dörmann, Ulrike; Micke, Florian; Filipovic, André; Kleinöder, Heinz; Donath, Lars (Frontiers in Physiology, 2019)
Background: Whole-body electromyostimulation (WB-EMS) gained increasing interest in sports within recent years. However, few intervention studies have examined the effects of WB-EMS on trained subjects in comparison to conventional strength training. Objective: The aim of the present mini-meta-analysis of 5 recently conducted and published randomized controlled WB-EMS trails of our work group was to evaluate potentially favorable effects of WB-EMS in comparison to conventional strength training. Methods: We included parameter of selected leg muscle's strength and power as well as sprint and jump performance. All subjects were moderately trained athletes [>2 training sessions/week, >2 years of experience in strength training; experimental group (n = 58): 21.5 ± 3.3 y; 178 ± 8 cm; 74.0 ± 11 kg; control group (n = 54): 21.0 ± 2.3 y; 179.0 ± 9 cm; 72.6 ± 10 kg]. The following WB-EMS protocols were applied to the experimental group (EG): 2 WB-EMS sessions/week, bipolar current superimposed to dynamic exercises, 85 Hz, 350 μs, 70% of the individual pain threshold amperage. The control groups (CG) underwent the same training protocols without WB-EMS, but with external resistance. Results: Five extremely homogenous studies (all studies revealed an I2 = 0%) with 112 subjects in total were analyzed with respect to lower limb strength and power in leg curl, leg extension and leg press machines, sprint—and jump performance. Negligible effects in favor of WB-EMS were found for Fmax of leg muscle groups [SMD: 0.11 (90% CI: −0.08, 0.33), p = 0.73, I2 = 0%] and for CMJ [SMD: 0.01 (90% CI: −0.34, 0.33), p = 0.81, I2 = 0%]. Small effects, were found for linear sprint [SMD: 0.22 (90% CI: −0.15, 0.60), p = 0.77, I2 = 0%] in favor of the EMS-group compared to CON. Conclusion: We conclude that WB-EMS is a feasible complementary training stimulus for performance enhancement. However, additional effects on strength and power indices seem to be limited and sprint and jump-performance appear to be benefiting only slightly. Longer training periods and more frequent application times and a slightly larger stimulus could be investigated in larger samples to further elucidate beneficial effects of WB-EMS on performance parameters in athletes.